2001
DOI: 10.1007/pl00000238
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens ameliorate remote organ inflammation induced by burn injury in rats

Abstract: We propose that treatment with estrogens or antiandrogens might be applicable in clinical situations to ameliorate systemic inflammation induced by burn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…In addition to a decrease in MPO, estrogen treatment significantly reduced burn-induced innate cell infiltration in the liver and lung. The androgen receptor blocker, cyproterone acetate, reduced MPO levels but not as effectively as estrogen treatment but this may be due to a suboptimal blockade of the androgen receptor [47]. These and other studies show that both testosterone and estrogen play a role in leukocyte recruitment and effector function.…”
Section: Neutrophilsmentioning
confidence: 67%
See 2 more Smart Citations
“…In addition to a decrease in MPO, estrogen treatment significantly reduced burn-induced innate cell infiltration in the liver and lung. The androgen receptor blocker, cyproterone acetate, reduced MPO levels but not as effectively as estrogen treatment but this may be due to a suboptimal blockade of the androgen receptor [47]. These and other studies show that both testosterone and estrogen play a role in leukocyte recruitment and effector function.…”
Section: Neutrophilsmentioning
confidence: 67%
“…This enzyme is often used as an index of neutrophil activation or content. MPO activity induced by burn injury was significantly reduced following castration of male mice [47]. In addition to a decrease in MPO, estrogen treatment significantly reduced burn-induced innate cell infiltration in the liver and lung.…”
Section: Neutrophilsmentioning
confidence: 89%
See 1 more Smart Citation
“…[53] Accordingly, in another study, diminishing TNF-a expression significantly reduced ischemia-induced renal fibrosis and inflammation and improved renal functions. [54] On the other hand, the administration of E 2 depressed elevations in serum TNF-a levels following burn-injury [22] or trauma-hemorrhage. [55] In addition, E 2 inhibited the production of TNF-a by the unstimulated and hydrogen peroxide-stimulated macrophages from males and females.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that 17b-estradiol (E 2 ) protects the liver and intestines against sepsis-induced damage, [20] improves the healing of gastric and colonic injury, [21] and ameliorates burn-induced liver and lung injury in rats. [22] However, the effect of E 2 treatment on the oxidative complications of CRF has not (to our knowledge) been previously addressed.…”
Section: Introductionmentioning
confidence: 94%